2015
DOI: 10.3311/ppci.7092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonlinear Resilient Models of Unbound Aggregates on Analysis and Performance of Road Pavements

Abstract: Proper characterisation of the mechanical properties of unbound granular materials (UGM) is an essential issue in the IntroductionLow to moderate volume roads in Algeria cover more than 70% of the total road network of the country [1]. These road structures typically consist of thin asphalt layers and structurally significant unbound base and sub-base granular layers over subgrade to carry the traffic load. It follows that accurate modelling of granular layer behaviour is of crucial importance for the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since the goal was to recreate the regression coefficients as functions of basic soil parameters, grain size distribution and Proctor tests were carried out to determine the soil properties applicable in those equations. The research results that can be found in the literature [5,6] indicate well what are those parameters that are worth trying to assemble such equations, and what is the logic behind the assessment.…”
Section: Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the goal was to recreate the regression coefficients as functions of basic soil parameters, grain size distribution and Proctor tests were carried out to determine the soil properties applicable in those equations. The research results that can be found in the literature [5,6] indicate well what are those parameters that are worth trying to assemble such equations, and what is the logic behind the assessment.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…This model is called k 1 -k 3 or universal model in practice, and its main advantage is that it could take into consideration the change of the stress state [4][5][6].…”
Section: Introductionmentioning
confidence: 99%